Anti-Tumorigenic Activities of IL-33: A Mechanistic Insight - Andreone, Sara; Gambardella, Adriana Rosa; Mancini, Jacopo; Loffredo, Stefania; Marcella, Simone; La Sorsa, Valentina; Varricchi, Gilda; Schiavoni, Giovanna; Mattei, Fabrizio (Frontiers in Immunology, 2020)
Interleukin-33 (IL-33) is an epithelial-derived cytokine that can be released upon tissue damage, stress, or infection, acting as an alarmin for the immune system. IL-33 has long been studied in the context of Th2-related immunopathologies, such as allergic diseases and parasitic infections. However, its capacity to stimulate also Th1-type of immune responses is now well established. IL-33 binds to its specific receptor ST2 expressed by most immune cell populations, modulating a variety of responses. In cancer immunity, IL-33 can display both pro-tumoral and anti-tumoral functions, depending on the specific microenvironment. Recent findings indicate that IL-33 can effectively stimulate immune effector cells (NK and CD8+ T cells), eosinophils, basophils and type 2 innate lymphoid cells (ILC2) promoting direct and indirect anti-tumoral activities. In this review, we summarize the most recent advances on anti-tumor immune mechanisms operated by IL-33, including the modulation of immune checkpoint molecules, with the aim to understand its potential as a therapeutic target in cancer.